Logistik Perkotaan Pintar di Provinsi DKI Jakarta: Sebuah Pendekatan Causal Loop Diagram - Vikaliana, Resista; Raza, Erwin; Sutandi, Sutandi (LPPM Universitas Jambi, 2022)
Well-managed logistics activities will support the economic sustainability of a region. There are three important elements that need to be improved to create an efficient and efficient flow of goods distribution in urban areas, namely transportation facilities, actors, and other matters related to the urban context. At the same time, these elements must also be synergized with local government policies involving economic, transportation, infrastructure and environmental issues. This research will develop Smart Urban Logistics in DKI Jakarta, as the area with the highest congestion. The purpose of this study is to recommend a smart urban logistics model in the supply chain of goods in DKI Jakarta and to develop a smart urban system policy scenario in DKI Jakarta. Meanwhile, the urgency of this research is to contribute to increasing the mobility of goods and values. This research also has implications for sustainable mobility/mobility in the supply chain of goods in DKI Jakarta Province. In this study, the Causal Loop Diagram (CLD) approach was used to answer the research objectives. CLD helps understand what to do and where to start a system, which in this study is smart goods logistics. Although the Causal Loop Diagram (CLD) approach has helped to determine the identification, further research is needed to simulate a system similar to the actual system.